Examining Factors of Murobahah Financing Margin Revenue in Indonesian Sharia Banking - Ubaedilah Ubaedilah; Abdul Aziz (Journal of Islamic Economic Scholar, 2022)
The purpose of this study was to determine the effect of the BI-7 Day Repo rate and third party funds on the murabahah margin income of Islamic commercial banks in Indonesia. This research data uses secondary data in the form of the 2016-2020 Islamic commercial bank annual report. The total population used is 6 Islamic commercial banks registered with the Financial Services Authority during the 2016–2020 period. Sampling using purposive sampling technique and data processing using the Eviews 9 application. The results showed that third party funds had a significant positive effect on murabahah margin income. However, the bi – 7 Day repo rate shows a less significant effect